Advancing two‐component partitioning of light scattering in Cayuga Lake, New York. (27th October 2015) - Peng, Feng; Effler, Steven W.
Abstract: The particulate scattering and backscattering coefficients ( b p and b bp ) were partitioned into the additive contributions of minerogenic ( b m and b b, m ) and organic ( b o and b b, o ) components for nearshore and pelagic areas of Cayuga Lake, New York, over a 7 month period in 2013. The analysis was based on paired measurements of (1) bulk b p and b bp, (2) light‐scattering properties of mineral particles, with an individual particle analysis (IPA) technique, and (3) concentrations of chlorophyll a ([Chl]) and particulate organic carbon (POC), as two indices to quantify organic particle scattering. b m and b b, m were estimated through Mie theory calculations with IPA results as inputs. b o and b b, o were estimated with both system‐specific and oceanic bio‐optical models parameterized on [Chl] or POC. POC performed better than [Chl] as the index for both b o and b b, o . The averages of the ratios ( b m  +  b o ) :  b p and ( b b, m  +  b b, o ) :  b bp at 660 nm, were 1.02 and 1.03, respectively; the average relative errors were 18.2% and 15.6%. Multiple empirical bio‐optical models developed for Case 1 oceanic waters (for b o and b b, o estimates) approached the closure performance of the system‐specific relationships. In addition to systematically accounting for more b bp than b p, terrigenous minerogenic particles made greater contributions to both b p and b bp in the nearshore area proximate to tributary inputs than in pelagic waters. A strong positive dependency of the backscattering ratio ( b bp  :  b p ) on the b m  :  b p ratio was observed for both nearshore and pelagic areas.